The Crisis of Leadership Succession in Nahdlatul Ulama: An Institutional Analysis of the Uncertainty of Leadership Transition, Duplication in Leadership Training, the Transmission of Identity, and Imbalances in the Organizational Structure - Hamdan Adib; Saefullah (Journal of Nahdlatul Ulama Studies, 2026)
Nahdlatul Ulama (NU) possesses extensive organizational networks, human resources, and a large socio-religious constituency, making cadre regeneration essential for organizational sustainability. However, several challenges indicate that the regeneration system has not functioned optimally. This study aims to analyze the crisis of cadre regeneration in Nahdlatul Ulama from an institutional perspective, focusing on four issues: unclear cadre transition among autonomous bodies, duplication of cadre education, inheritance of identity without organizational participation, and disparities in organizational structures between Java and regions outside Java. This research employed a qualitative library research approach. Primary data were obtained from the Constitution and Bylaws (AD/ART) of Nahdlatul Ulama and its autonomous organizations, while secondary data were collected from relevant literature and supporting documents. Data were analyzed using content analysis. The findings reveal that the NU regeneration system has achieved structural institutionalization but has not yet reached systemic integration. As a result, cadre mobility remains fragmented, cadre education tends to be repetitive, organizational participation is not effectively reproduced across generations, and cadre development remains uneven across regions. The novelty of this study lies in proposing an integrated regeneration model based on a sustainable cadre pipeline, competency recognition, family-based regeneration, and affirmative policies for strengthening cadre development outside Java. These findings contribute to strengthening organizational sustainability and leadership succession within Nahdlatul Ulama.